Neighborhood at your Fingertips: Transforming Community Online through a Canadian Social Networking Site for Mothers. (July 2014) - Valtchanov, Bronwen L.; Parry, Diana C.; Glover, Troy D.; Mulcahy, Caitlin M.
Local geographical communities have changed significantly in the last several decades due to a number of cultural factors, including women's increased participation in the paid workforce and growing rates of single parenthood. Changing communities have resulted in increased social isolation for mothers raising young children, which often means a lack of vital social support, particularly from other mothers. The current research addresses this contemporary challenge by exploring the role of a Canadian social networking site for mothers, namely, Momstown.ca, in providing online social support to mothers. In particular, the study focuses on how the dynamic possibilities of technology mediate the experience of motherhood. Our research demonstrates that a social networking site, which facilitated a technologically mediated motherhood, enabled women to combat their social isolation through the creation of an accessible and supportive online community of mothers. The distinctive ease, convenience, and speed of online connectivity, combined with the respectfulness cultivated within this particular online community, facilitated mothers' access to essential peer support in the forms of emotional sustenance, "appraisal assistance, " and informational resources. Mothers' engagement with this online community was ultimately an empowering experience that speaks of the transformative possibilities of cyberfeminism.